Penggunaan Bayangan untuk Menentukan Waktu Shalat: Kajian Tafsir Al-Qur’an terhadap Kitab Ifrad Al-Maqal Fi Amr Az-Zilal Karya Al-Biruni - Anisah Ramadhani Saragih; Hasyimsyah Nasution (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the use of shadows (az-zilal) to determine prayer times through an exegetical analysis of the book Ifrad al-Maqal fi Amr az-Zilal by Abu Rayhan al-Biruni. The prevailing dichotomy of knowledge has led to Qur’anic verses on the theme of shadows being studied solely through linguistic or jurisprudential lenses, without involving quantitative verification through astronomical instruments. This research is a library-based study employing the thematic exegesis (tafsir maudhu’i) method and the scientific exegesis (tafsir ilmi) approach, using content analysis of E. S. Kennedy’s translation. The findings reveal that among all the Qur’anic quotations in Ifrad al-Maqal, there are four groups of verses that directly integrate the phenomenon of shadows with the determination of prayer times: QS. Al-Furqan [25]:45–46; QS. An-Nahl [16]:48 and QS. Ar-Ra’d [13]:15; QS. Al-Isra’ [17]:78; and QS. Hud [11]:114. These verses serve not only as theological legitimization but also as epistemological premises that al-Biruni transformed into a shadow trigonometry system utilizing the functions zill mustawi (cotangent) and zill ma’kus (tangent) to formulate precise boundaries for the Zuhr and Asr prayer times. This study affirms that al-Biruni is a pioneer of the scientific exegesis methodology that employs mathematics as an instrument of verification for the scientific indications of the Qur’an.